Sociedad y crisis de valores : interrogantes y respuestas desde la bioética y la biojurídica - Cárdenas Krenz, Arturo Ronald (2014)
The article is a reflection on the current world from the perspective of Bioethics and Law, taking into account the importance of an ethical approach considering the commodification of human life, several new technology-related developments, and value crisis of our times, emphasizing on the need for a humanistic approach to address them.